Enzyme and cofactor engineering to increase d-xylonate dehydratase activity for improved d-1,2,4-butanetriol production from d-xylose - Jingwen Chen; Zhangyu Liu; Dandan Mai; Sheng Xu; Xin Wang; Kequan Chen (Synthetic and Systems Biotechnology)
d-1,2,4-Butanetriol (BTO), a C4 platform compound, is widely used in fields such as military and pharmaceuticals. Biosynthesis of d-1,2,4-BTO from lignocellulose-derived d-xylose presents a promising production route. However, the low catalytic activity of d-xylonate dehydratase leading to the accumulation of d-xylonic acid remains a key bottleneck for the efficient production of d-1,2,4-BTO. In this study, we aimed to enhance the catalytic activity of d-xylonate dehydratase through an integrated enzyme and cofactor engineering approach. Firstly, we evolved the d-xylonate dehydratase YjhG by using both random mutagenesis and site-directed saturation mutagenesis. Among the generated variants, YjhGT325F showed an 1.82-fold increase in d-xylonic acid consumption compared to the wild-type enzyme. When introduced into the producing strain, this variant increased d-1,2,4-BTO production by 1.34-fold compared to the original strain. Further enhancement was achieved by modifying the iron-sulfur [Fe–S] cluster synthesis system, which was critical for d-xylonate dehydratase activity. We systematically evaluated three [Fe–S] assembly systems, including SUF (encoded by sufABCDSE), ISC (encoded by iscSUA-hscBA-fdx), and CSD (encoded by csdAE). Comparative analysis revealed that the overexpression of SUF system conferred the highest catalytic efficiency of YjhG. The recombinant strain of BT-YjhGT325F-SUF produced 10.36 g/L of d-1,2,4-BTO from d-xylose, achieving a molar yield of 73.6 %, which was 1.88-fold that of the original strain. This study provided a robust foundation for high-efficiency d-1,2,4-BTO production through enzyme and cofactor engineering.